Evaluasi Efisiensi Ekonomi dan Dampak Investasi dari Penerapan Metode Pembelajaran Praktikum Fisika dalam Meningkatkan hasil Belajar Siswa di SMA Negeri 2 Lhokseumawe - Cut Keumala Sari (Yayasan Kawanad, 2023)
This research aims to evaluate the economic efficiency and investment impact of implementing the Physics Practicum Learning Method to enhance student learning outcomes at SMA Negeri 2 Lhokseumawe. The practicum method is designed to provide direct experiences to students, enabling them to apply theoretical knowledge in practical situations. In this study adopts an economic evaluation approach, analyzing how the utilization of educational resources, including teacher time, and practicum facilities, can yield superior learning outcomes compared to conventional teaching methods The research involves quantitative data collection through surveys, practicum observations, and student learning outcome evaluations. Economic analysis is conducted to assess the educational investment by considering operational costs and benefits obtained. The research findings are expected to provide in-depth insights into the efficiency of the Physics Practicum Learning Method in the educational at SMA Negeri 2 Lhokseumawe. Practical implications of these results may assist policymakers and education practitioners in enhancing physics education quality, considering the economic aspects involved.